Negative electrode and lithium-ion secondary battery
Patent Information
- Application Number
- JP2025057612
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0021】 本発明の負極によれば、サイクル試験時の反応抵抗を低減できる。
Smart Images

Figure 2026165292000002 
Figure 2026165292000003 
Figure 2026165292000001
Abstract
Description
[Technical Field]
[0001] This invention relates to a negative electrode and a lithium-ion secondary battery. [Background technology]
[0002] In all-solid-state batteries, maintaining electron and ion conduction paths at the interface between the active material and the solid electrolyte is necessary to achieve the expected capacity, resistance, and durability during repeated charging and discharging cycles. However, when using silicon-based active materials as the negative electrode active material, large volume fluctuations in the active material during charging have led to interfacial delamination between the negative electrode active material and the solid electrolyte. This interfacial delamination disrupts electron and ion conduction paths, resulting in performance degradation.
[0003] As a method to eliminate interfacial delamination, efforts have been made to improve the bonding area at the interface between the active material and the solid electrolyte by using a coated active material in which a solid electrolyte is coated on the surface of the active material (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] International Publication No. 2023 / 198886 [Patent Document 2] U.S. Patent Application Publication No. 2020 / 0373580 [Patent Document 3] Patent No. 7251069 [Patent Document 4] U.S. Patent No. 11223036 [Overview of the project] [Problems that the invention aims to solve]
[0005] In methods where a solid electrolyte is coated onto the surface of an active material, the effect of reducing resistance at the interface between the active material and the solid electrolyte has been reported. However, against the expansion and contraction of the active material, peeling is observed between the coated active material and the solid electrolyte in the electrode that is in contact with the coated active material, and there has been an issue with the reaction resistance during cycle testing.
[0006] The present invention has been made to solve the above problems, and aims to provide a negative electrode capable of reducing reaction resistance during cycle testing, and a lithium ion secondary battery provided with the negative electrode. Further, it contributes to the improvement of energy efficiency. Means for Solving the Problems
[0007] To achieve the above object, the present invention provides the following means. [1]A negative electrode comprising a silicon-based active material and a solid electrolyte, wherein at least a part of the surface of the active material is coated with a coating layer, and the coating layer contains a metal element capable of forming an alloy with lithium.
[0008] In the negative electrode according to [1], at least a part of the surface of the active material is coated with a coating layer containing a specific metal element. For this reason, peeling between the active material and the solid electrolyte accompanying expansion and contraction of the active material can be suppressed, and the reaction resistance during cycle testing can be reduced. Therefore, energy loss can be reduced, contributing to improved energy efficiency.
[0009] [2]The negative electrode according to [1], wherein the metal element is at least any one of Ni, In, Sb and Bi.
[0010] In the negative electrode according to [2], the specific metal element contained in the coating layer is at least any one of Ni, In, Sb and Bi. For this reason, peeling between the active material and the solid electrolyte can be further suppressed, and the reaction resistance during cycle testing can be further reduced. Therefore, energy loss can be further reduced, contributing to further improved energy efficiency.
[0011] [3]The negative electrode according to [1] or [2], wherein the thickness of the coating layer is 10 nm or more and 100 nm or less.
[0012] The negative electrode in [3] has a coating layer thickness that satisfies a specific numerical range. Therefore, delamination between the active material and the solid electrolyte can be further suppressed, and reaction resistance during cycle testing can be further reduced. Consequently, energy loss can be further reduced, contributing to even greater energy efficiency.
[0013] [4] The negative electrode according to [1] or [3], wherein the metal element is Sb.
[0014] In the negative electrode described in [4], the specific metal element contained in the coating layer is Sb. Therefore, delamination between the active material and the solid electrolyte can be further suppressed, and reaction resistance during cycle testing can be further reduced. Consequently, energy loss can be further reduced, contributing to even greater energy efficiency.
[0015] [5] The negative electrode according to any one of [1] to [4], wherein the solid electrolyte is a sulfide solid electrolyte.
[0016] The negative electrode in [5] has a sulfide solid electrolyte. Therefore, the separation between the active material and the solid electrolyte can be further suppressed, and the reaction resistance during cycle testing can be further reduced. Consequently, energy loss can be further reduced, contributing to further energy efficiency.
[0017] [6] The negative electrode according to any one of [1] to [5], wherein the active material is a composite material of silicon and a different element from silicon.
[0018] The negative electrode in [6] is a composite material in which the active material is silicon and a different element from silicon. Therefore, delamination between the active material and the solid electrolyte can be further suppressed, and reaction resistance during cycle testing can be further reduced. Consequently, energy loss can be further reduced, contributing to further energy efficiency.
[0019] A lithium-ion secondary battery comprising a negative electrode as described in any of [7], [1] to [6], a positive electrode, and a solid electrolyte layer.
[0020] The lithium-ion secondary battery according to [7] is equipped with a negative electrode as described in any of [1] to [6]. Therefore, separation of the active material and the solid electrolyte due to the expansion and contraction of the active material can be suppressed, and the reaction resistance during cycle testing can be reduced. Consequently, energy loss can be reduced, and energy efficiency can be improved. [Effects of the Invention]
[0021] The negative electrode of the present invention can reduce reaction resistance during cycle testing. [Brief explanation of the drawing]
[0022] [Figure 1] This is a schematic cross-sectional view showing the configuration of a lithium-ion secondary battery according to one embodiment of the present invention. [Figure 2] This is a schematic diagram showing the overall structure of a silicon-based active material and coating layer according to one embodiment of the present invention. [Modes for carrying out the invention]
[0023] Preferred embodiments of the present invention will be described in detail below.
[0024] [Lithium-ion rechargeable battery] Figure 1 is a cross-sectional view of a lithium-ion secondary battery (hereinafter also referred to as "battery") 1 according to one embodiment of the present invention. As shown in Figure 1, the battery 1 comprises a positive electrode 10, a negative electrode 20, and a solid electrolyte layer 30. The battery 1 is a laminate in which the positive electrode 10, the solid electrolyte layer 30, and the negative electrode 20 are stacked in this order. In this specification, the term "battery" refers to an all-solid-state battery or a semi-solid-state battery.
[0025] <Positive electrode> The positive electrode 10 comprises a positive electrode layer 11 and a positive electrode current collector 12. The positive electrode layer 11 is located on the solid electrolyte layer 30 side. The positive electrode current collector 12 constitutes the surface on the positive electrode 10 side of the battery 1. Although not specifically shown in the figures, it is preferable that the battery 1 has a known casing.
[0026] The positive electrode layer 11 contains a positive electrode active material. The positive electrode active material used in the positive electrode layer 11 is not particularly limited, and may be any material that functions as the positive electrode of the battery 1. Note that specific examples of the positive electrode active material include, for a lithium ion battery, layered active materials containing lithium, spinel-type active materials, olivine-type active materials, and the like. Specific examples of the positive electrode active material include lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), LiNi p Mn q Co r O2(p+q+r=1), LiNi p Al q Co r O2(p+q+r=1), lithium manganate (LiMn2O4), Li (1+x) Mn (2-x-y) M y O4(x+y=2, M is at least one selected from the group consisting of Al, Mg, Co, Fe, Ni, and Zn), heteroelement-substituted Li-Mn spinel represented by the formula, lithium titanate (oxide containing Li and Ti), lithium metal phosphate (LiMPO4, M is at least one selected from the group consisting of Fe, Mn, Co, and Ni), and the like. It is also possible to use a mixture of these.
[0027] The positive electrode layer 11 may contain a solid electrolyte, a conductive material, and a binder in addition to the positive electrode active material. The solid electrolyte, the conductive material, and the binder will be described later.
[0028] The proportion of the positive electrode active material in the positive electrode layer 11 is, for example, preferably 20% by mass or more, may be 30% by mass or more, may be 40% by mass or more, and may be 50% by mass or more. On the other hand, the proportion of the positive electrode active material is, for example, preferably 99% by mass or less, may be 90% by mass or less, may be 80% by mass or less, may be 70% by mass or less, and may be 60% by mass or less.
[0029] The thickness of the positive electrode layer 11 is not particularly limited and can be set appropriately according to the desired battery performance. For example, the thickness of the positive electrode layer 11 may be in the range of 0.1 μm to 1000 μm.
[0030] The positive electrode current collector 12 has the function of collecting current from the positive electrode layer 11. The positive electrode current collector 12 is a foil-shaped member made of a conductive electrode material. The electrode material used for the positive electrode current collector 12 is not particularly limited as long as it is a conductive material, and examples include aluminum, aluminum alloy, stainless steel, nickel, iron, and titanium. Preferably, the electrode material used for the positive electrode current collector 12 is at least one selected from the group consisting of aluminum, aluminum alloy, and stainless steel.
[0031] The shape and thickness of the positive electrode current collector 12 are not particularly limited, as long as they are capable of collecting current from the positive electrode layer 11. Examples of the shape of the positive electrode current collector 12 include foil-like and plate-like shapes.
[0032] <Negative electrode> The negative electrode 20 comprises a negative electrode layer 21 and a negative electrode current collector 22. The negative electrode layer 21 is located on the solid electrolyte layer 30 side. The negative electrode current collector 22 constitutes the surface on the negative electrode 20 side of the battery 1. One feature of the present invention is that the negative electrode layer 21 includes a silicon-based active material whose surface is covered with a coating layer, and a solid electrolyte.
[0033] According to the present invention, by using a coated active material coated with a coating layer as the negative electrode active material, delamination between the active material and the solid electrolyte due to the expansion and contraction of the active material during charging and discharging can be suppressed, and the reaction resistance during cycle testing can be reduced. The performance of a battery is greatly influenced by the bonding state of the solid-solid interface between the active material, conductive material, and solid electrolyte. On the other hand, silicon-based active materials are, for example, next-generation materials that enable rapid charging, but because the volume change due to charging and discharging is large, it is difficult to maintain a strong solid-solid interface. In contrast, in the present invention, at least a part of the surface of the active material is coated with a coating layer containing a specific metal element. Therefore, delamination between the active material and the solid electrolyte due to the expansion and contraction of the active material can be suppressed, and the reaction resistance during cycle testing can be reduced. As a result, a strong solid-solid interface can be maintained, and battery characteristics such as cycle characteristics and capacity characteristics can be improved.
[0034] The negative electrode layer 21 contains a silicon-based active material as the negative electrode active material. The silicon-based active material is preferably an active material that can be alloyed with Li. Examples of silicon-based active materials include elemental silicon, silicon alloys, silicon oxides, and composite materials containing silicon and other dissimilar elements. Examples of silicon alloys include SiC, SiN, SiTi, SiAl, SiLi, SiCu, etc., and examples of silicon oxides include SiO, etc. Examples of composite materials containing silicon and other dissimilar elements include silicon-lithium composite materials, silicon-carbon composite materials, and silicon-aluminum composite materials. The composite material containing silicon and other dissimilar elements may be a silicon alloy or not.
[0035] The negative electrode active material is preferably a composite material containing silicon and a different heterogeneous element. A composite material containing silicon and a different heterogeneous element has a structure in which the heterogeneous element mitigates the effects of expansion and contraction of silicon during charging and discharging. Therefore, it is possible to mitigate volume changes due to expansion and contraction with respect to the silicon active material. Due to this structure, delamination between the active material and the solid electrolyte can be further suppressed, and reaction resistance during cycle testing can be further reduced.
[0036] The negative electrode layer 21 may contain only silicon-based active materials as the negative electrode active material, or it may contain other active materials. In the latter case, the proportion of silicon-based active materials in all negative electrode active materials may be 50% by mass or more, 70% by mass or more, or 90% by mass or more.
[0037] <Coating layer> At least a portion of the surface of the silicon-based active material is covered by a coating layer. That is, the negative electrode layer 21 may contain, as the negative electrode active material, a silicon-based active material and a coated active material having a coating layer that covers the surface of the silicon-based active material and contains a specific metal element. The presence of a coating layer on the surface of the silicon-based active material can suppress delamination between the active material and the solid electrolyte due to the expansion and contraction of the active material, thereby reducing reaction resistance during cycle testing.
[0038] The coating layer contains metallic elements. The metal element in question is a metal element capable of forming an alloy with lithium. Preferably, such a metal element is one that is readily available in practice, such as Ni, In, Sb, Bi, Cu, Zn, Ga, Ge, As, Pd, Cu, Ag, Al, Cd, Sn, Pt, Au, Tl, Pb, P, As, etc.
[0039] Preferred metal elements in the coating layer are Ni, In, Sb, and Bi. This provides flexibility to the coating layer, making it easier to follow volume changes of the active material and contributing to strengthening the conduction paths of electrons and ions.
[0040] Sb is more preferable as the metal element included in the coating layer. Because Sb has high ionic conductivity, it is more likely to contribute to strengthening electron and ion conduction paths compared to coating layers containing other metal elements.
[0041] Furthermore, the coating layer may contain an alloy of a metal element and Li, or an alloy of Sb and Li. Compared to other alloys, the Sb-Li alloy has a lower coefficient of expansion, is more flexible, and can easily follow the volume changes of the active material. For this reason, it is thought to be effective in suppressing delamination between the active material and the solid electrolyte.
[0042] The thickness of the coating layer is preferably 10 nm to 100 nm, more preferably 15 nm to 80 nm, even more preferably 18 nm to 60 nm, and particularly preferably 20 nm to 40 nm. If the thickness of the coating layer is greater than or equal to the lower limit, the strength of the coating layer can be increased, the conduction paths for electrons and ions can be maintained, and the increase in resistance can be suppressed. If the thickness of the coating layer is less than or equal to the upper limit, the increase in resistance due to the coating layer having lower ionic conductivity than the solid electrolyte can be suppressed. On the other hand, if the thickness of the coating layer is less than the lower limit, the strength of the coating layer is insufficient, the conduction paths for electrons and ions cannot be maintained, and the increase in resistance cannot be suppressed. Furthermore, if the thickness of the coating path exceeds the upper limit, the coating layer itself becomes a resistive layer and the resistance increases. The thickness of the coating layer can be determined from a cross-sectional SEM image obtained by observing the cross-section of the active material and the coating layer with a scanning electron microscope (SEM).
[0043] Regarding the mass ratio of the active material to the metal element, it is preferable that the ratio of active material to metal element is 6:1 to 10:1, and more preferably 7:1 to 9:1. When the mass ratio of the active material to the metal element is within the above numerical range, the thickness of the coating layer can be controlled to the above-mentioned preferred range, and delamination between the active material and the solid electrolyte can be suppressed. Regarding the volume ratio of active material to metal element, it is preferable that the ratio of active material to metal element is 7:1 to 23:1, and more preferably 10:1 to 20:1. When the volume ratio of active material to metal element is within the above numerical range, the thickness of the coating layer can be controlled to the above-mentioned preferred range, and delamination between the active material and the solid electrolyte can be suppressed.
[0044] The proportion of the negative electrode active material in the negative electrode layer 21 is preferably 20% by mass or more, may be 30% by mass or more, may be 40% by mass or more, or may be 50% by mass or more. On the other hand, the proportion of the negative electrode active material is preferably 99% by mass or less, may be 90% by mass or less, may be 80% by mass or less, may be 70% by mass or less, or may be 60% by mass or less.
[0045] The negative electrode layer 21 contains a solid electrolyte. Here, in order to distinguish it from the solid electrolyte contained in the solid electrolyte layer 30 described later, the solid electrolyte contained in the negative electrode layer 21 is referred to as the first solid electrolyte.
[0046] Examples of primary solid electrolytes include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halogen solid electrolytes.
[0047] Sulfide solid electrolytes typically contain a metal element (M) that acts as a conductive ion and sulfur (S). Examples of M include Li, Na, K, Mg, Ca, etc., and in this embodiment, where Li ion conductivity is required, Li is used. In particular, the sulfide solid electrolyte of this embodiment preferably contains Li, A (where A is at least one selected from the group consisting of P, Si, Ge, Al, and B), and S. Furthermore, A is preferably P (phosphorus). In addition, the sulfide solid electrolyte may contain halogens such as Cl, Br, and I from the viewpoint of improving ionic conductivity. Furthermore, the sulfide solid electrolyte may contain O (oxygen).
[0048] Because sulfide solid electrolytes have high ionic conductivity, even if some of the multiple ion conduction paths are interrupted during a cycle test, ion conduction is maintained in the remaining paths, resulting in suppressed reaction resistance. Furthermore, the sulfide solid electrolyte has flexibility, and even when the volume of the coated active material changes, interfacial peeling or cracking is less likely to occur between the sulfide solid electrolyte and the coating layer, and the sulfide solid electrolyte can follow the volume change of the active material together with the coating layer, so that the occurrence of interfacial peeling and cracking can be further suppressed.
[0049] Examples of the sulfide solid electrolyte of the present embodiment having Li ion conductivity include, for example, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (provided that m and n are positive numbers, and Z is any one of Ge, Zn and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (provided that x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga and In), Li v P w S x Cl y Br z (v, w, x, y, z>0) and the like can be used. From the viewpoint of maintaining ion conductivity even during a cycle test and reducing reaction resistance, Li v P w S x Cl y Br z (0<v<10, 0<w<5, 0<x<5, 0<y<5, 0<z<5) is preferably used, and Li 5.4 PS 4.4 Cl 0.8 Br 0.8 and the like can be used. The above description of "Li2S-P2S5" means a sulfide solid electrolyte formed using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0050] Furthermore, the sulfide solid electrolyte may be sulfide glass or crystalline sulfide glass, or a crystalline material obtained by a solid-phase method. Sulfide glass can be obtained, for example, by performing a mechanical milling method (for example, a method of milling using a ball mill) on the raw material composition. Crystalline sulfide glass can be obtained, for example, by heat-treating sulfide glass at a temperature above its crystallization temperature.
[0051] The sulfide solid electrolyte is preferably an argyrodite-type sulfide solid electrolyte. Argyrodite-type sulfide solid electrolytes are flexible, and even if the volume of the coating active material changes, interfacial delamination and cracking are less likely to occur between them and the coating layer. Because they can follow the volume changes of the active material together with the coating layer, the occurrence of interfacial delamination and cracking can be further suppressed.
[0052] In addition to the inorganic solid electrolytes mentioned above, oxide solid electrolytes or organic solid electrolytes may be used as the first solid electrolyte. Examples of oxide solid electrolytes include solid electrolytes containing Li, Y (where Y is at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Examples of organic solid electrolytes include polymer-based solid electrolytes such as polyethylene oxide polymer compounds, polymer compounds containing at least one polyorganosiloxane chain or polyoxyalkylene chain, fluorine-based polymer compounds, and polyurethane-based polymer compounds.
[0053] The shape of the first solid electrolyte can be particulate, for example. The average particle size of the first solid electrolyte is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more. On the other hand, the average particle size of the first solid electrolyte is preferably 20 μm or less, more preferably 10 μm, even more preferably 1 μm or less, and particularly preferably 0.7 μm or less. If the average particle size of the first solid electrolyte is less than 0.05 μm, when forming a coating layer with the solid electrolyte on the surface of the active material, the solid electrolytes will aggregate with each other, and a uniform coating layer will not be formed, making it impossible to suppress the separation of the active material and the solid electrolyte due to the expansion and contraction of the active material. Furthermore, if the average particle size of the first solid electrolyte exceeds 20 μm, the density of the coating layer will decrease, resulting in insufficient interface formation between the active material and the coating layer, making it impossible to suppress the separation of the active material and the solid electrolyte due to the expansion and contraction of the active material. The average particle size of the first solid electrolyte is D 50 It can be defined as such and can be calculated, for example, from measurements using a laser diffraction particle size analyzer or a scanning electron microscope (SEM). In the case of SEM measurements, a large number of samples is preferable, for example, 10 or more, but it may also be 50 or more, or even 100 or more. There is no particular upper limit to the number of samples, but for example, it can be 100,000 or less.
[0054] The proportion of the first solid electrolyte in the negative electrode layer 21 is preferably, for example, 1% by mass or more, may be 10% by mass or more, or 20% by mass or more. On the other hand, the proportion of the first solid electrolyte in the negative electrode layer 21 is preferably, for example, 60% by mass or less, may be 50% by mass or less, or 40% by mass or less.
[0055] The negative electrode layer 21 preferably contains a conductive material in addition to the first solid electrolyte, because this improves the electronic conductivity of the negative electrode layer 21. Examples of conductive materials include carbon materials and metallic materials. Examples of carbon materials include carbon black, acetylene black (AB), Ketjenblack (KB), carbon nanotubes (CNT), metallic carbon nanotubes (MCNT), semiconducting carbon nanotubes (SCNT), and carbon nanofibers (CNF). Examples of metallic materials include Ni, Cu, Fe, and SUS. Examples of conductive material shapes include spherical and fibrous shapes.
[0056] The proportion of conductive material in the negative electrode layer 21 is preferably 0.1% by mass or more, and may be 0.5% by mass or more. On the other hand, the proportion of conductive material in the negative electrode layer 21 is preferably 5% by mass or less, and may be 3% by mass or less.
[0057] The negative electrode layer 21 may contain a binder as needed. The binder is not particularly limited, but examples include fluorine-based binders such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), and fluororubber; and rubber-based binders such as butadiene rubber, hydrogenated butadiene rubber, styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, and ethylene propylene rubber. Acrylic binders may also be used.
[0058] The proportion of the binder in the negative electrode layer 21 is preferably 10% by mass or less, may be 5% by mass or less, or 3% by mass or less. On the other hand, the proportion of the binder in the negative electrode layer 21 is, for example, 0.1% by mass or more.
[0059] The thickness of the negative electrode layer 21 is preferably, for example, 0.1 μm or more and 1000 μm or less, more preferably 1 μm or more and 100 μm or less, and even more preferably 10 μm or more and 30 μm or less.
[0060] <Solid electrolyte layer> The solid electrolyte layer 30 is a layer formed between the positive electrode layer 11 and the negative electrode layer 21, and contains at least a solid electrolyte, and may contain a binder as needed. The solid electrolyte and binder are the same as those described above for the <negative electrode>, so they are omitted here. The thickness of the solid electrolyte layer 30 may be, for example, in the range of 0.1 μm or more and 1000 μm or less.
[0061] The battery in the present invention may be an all-solid-state battery or a semi-solid-state battery. An example of an all-solid-state battery is a battery having the solid electrolyte layer 30 described above. Examples of semi-solid batteries include batteries in which the electrolyte layer contains a semi-solid electrolyte. Examples of semi-solid electrolytes include electrolytes composed of polymer components and standard electrolytes. Examples of polymer components include polyvinylidene fluoride (PVDF) / polyethylene oxide (PEO), polyacrylonitrile (PAN) / PEO, polymethyl methacrylate (PMMA), PVDF / hexafluoropropylene (HFP), etc. Examples of standard electrolytes include 1 mol / L lithium hexafluorophosphate (LiPF6) EC / DMC solution, 1 mol / L LiPF6EC / ethyl methyl carbonate (EMC) solution, 1 mol / L LiPF6EC / DMC / EMC solution, etc.
[0062] [Battery manufacturing method] The present invention provides a method for manufacturing a battery, which involves first preparing a coated active material in which at least a portion of the surface of a silicon-based active material is coated with a coating layer (preparation step). Next, a negative electrode layer is formed using a negative electrode mixture containing the coated active material and a solid electrolyte (negative electrode layer step). Furthermore, a positive electrode layer and a solid electrolyte layer are formed based on known methods (positive electrode layer formation step, solid electrolyte layer formation step). A battery is obtained by stacking the positive electrode layer, solid electrolyte layer and negative electrode layer in this order. The order in which each layer is manufactured and the order in which each layer is stacked are not particularly limited.
[0063] According to the present invention, a battery with reduced reaction resistance during cycle testing can be obtained by forming a negative electrode layer using a coated active material coated with a coating layer.
[0064] <Preparation process> The preparation step involves preparing a coated active material in which the surface of the silicon-based active material is covered with a coating layer. In the preparation step, a coating treatment is performed to cover the surface of the silicon-based active material.
[0065] The coating procedure is as follows: (i) A silicon-based active material powder is placed inside a polygonal barrel fitted into a cylindrical vacuum container. (ii) The active material powder is stirred by rotating the polygonal barrel. (iii) The inside of the vacuum chamber is evacuated, and the inert gas is turned into plasma on the metal target. (iv) Plasma is collided with the metal target, causing metal particles to be emitted from the metal target. (v) Metal particles adhere to and coat the surface of the active material powder that is being stirred.
[0066] Unlike conventional sputtering, the coating process involves performing sputtering while rotating a cylindrical barrel (barrel sputtering). Specifically, the cylindrical barrel rotates, and stirring is performed by the swinging motion of a stirring arm. As a result, the surface of the active material powder is uniformly coated with metal, forming a coating layer with a uniform thickness.
[0067] The detailed conditions for the coating process are as follows: 《Detailed conditions》 • Spattering technique: Barrel spattering ·Active material input amount: 35g ·Ultimate pressure: 9.9×10 -4 Pa • Introduced gas: Ar • Operating pressure: 0.1 MPa Baking conditions: 100°C, 15 minutes • Agitation: Barrel swing RF sputtering power output: 80W • Film deposition time: 12 hours
[0068] <Negative electrode layer formation process> The negative electrode layer formation process is a process of forming the negative electrode layer using a negative electrode composite material containing a silicon-based active material and a first solid electrolyte on which a coating layer has been formed.
[0069] The negative electrode composite material contains at least a silicon-based active material with a coating layer formed on it and a first solid electrolyte, and may further contain at least one of a conductive material and a binder. That is, the negative electrode composite material contains the coating active material described above.
[0070] Furthermore, the negative electrode mixture may or may not contain a dispersion medium.
[0071] Any known method can be used to form the negative electrode layer. For example, one method for forming the negative electrode layer is to coat it with a negative electrode slurry and dry it. The negative electrode slurry can be obtained, for example, by kneading a negative electrode mixture (a negative electrode mixture containing a dispersion medium). Furthermore, a method is to form the negative electrode layer by pressing a layered negative electrode composite material.
[0072] <Other processes> The battery manufacturing method in this embodiment typically comprises a positive electrode layer formation step and a solid electrolyte layer formation step. Any known method can be used for forming the positive electrode layer and the solid electrolyte layer. Furthermore, the battery obtained by these steps is the same as that described above for [Lithium-ion secondary batteries].
[0073] This disclosure also provides a method for manufacturing a negative electrode active material for a solid-state battery, comprising the preparation steps described above. In this case, the negative electrode active material for the solid-state battery is preferably the coating active material described above. Furthermore, this disclosure also provides a method for manufacturing a negative electrode layer for a solid-state battery, comprising the preparation steps and the negative electrode layer formation steps described above.
[0074] A battery comprising the negative electrode containing the coating active material and solid electrolyte of this embodiment as described above provides the same effects as the negative electrode according to the embodiment described above.
[0075] It should be noted that the present invention is not limited to the embodiments described above, and any modifications or improvements that can achieve the objectives of the present invention are included within the scope of the present invention. [Examples]
[0076] The following describes embodiments of the present invention, but the present invention is not limited to the following embodiments.
[0077] <Example 1> [Preparation of coated active material] Antimony (Sb) was used as the metallic element for the coating process in the preparation stage. A composite material of silicon and carbon was used as the silicon-based active material powder, and sputtering was performed so that the mass ratio of the silicon-based active material to Sb was 6:1. 31.5 g of coated active material was obtained by barrel sputtering under the following detailed conditions. 《Detailed conditions》 ·Active material input amount: 35g ·Ultimate pressure: 9.9×10 -4 Pa • Introduced gas: Ar • Operating pressure: 0.1 MPa Baking conditions: 100°C, 15 minutes • Agitation: Barrel swing RF sputtering power output: 80W • Film deposition time: 12 hours
[0078] The obtained coated active material was embedded in epoxy resin and processed with an argon ion beam under an inert atmosphere to prepare cross-sectional samples. The surface of the cross-sectional samples was coated with Pd to prevent charge-up. The prepared cross-sectional samples were analyzed using scanning electron microscopy energy-dispersive X-ray spectroscopy (SEM-EDX). A scanning electron microscope (SEM) "SU8220" manufactured by Hitachi High Technologies, Inc. was used, and cross-sectional SEM observation was performed at an acceleration voltage of 2.0 kV. A schematic diagram showing the overall structure of the coated active material, obtained based on the cross-sectional SEM image, is shown in Figure 2.
[0079] As shown in Figure 2, it was confirmed that the coating active material 100 of this embodiment has a coating layer 60 formed over the entire surface of the silicon-based active material 50. EDX analysis confirmed that the coating layer contains Sb. Furthermore, cross-sectional SEM images confirmed that the thickness of the coating layer 60 shown in Figure 2 is approximately 20 nm.
[0080] <Examples 2-4, Comparative Example 1> The coated active material was obtained in the same manner as in Example 1, except that Ni (nickel) (Example 2), Bi (bismuth) (Example 3), and In (indium) (Example 4) were used as the metal elements in the coating process during the preparation step. Cross-sectional samples of the obtained coated active material were prepared in the same manner as in Example 1, and SEM-EDX analysis was performed. As a comparative example, a silicon-based active material without a coating layer was prepared (Comparative Example 1). The thickness of the coating layer for each example was determined from the cross-sectional SEM images, and the results are shown in Table 1. In Table 1, "-" indicates that no coating layer was formed.
[0081] [Fabrication of the negative electrode layer] The negative electrode layer was fabricated using the coating active material or silicon-based active material obtained in each example. A sulfide solid electrolyte, Li, was used as the solid electrolyte. 5.4 PS 4.4 Cl 0.8 Br 0.8The following was used: a fluorine-based binder was used as the binder, and carbon black was used as the conductive material. The mass ratio of the active material, solid electrolyte, binder, and conductive material in the negative electrode layer was (active material / solid electrolyte / binder / conductive material) = (70 / 27 / 2 / 1).
[0082] [Half-cell manufacturing] Sulfide solid electrolyte Li 5.4 PS 4.4 Cl 0.8 Br 0.8 After placing the material into a cylindrical ZrO2 tube, it was pressed between stainless steel jigs to obtain a solid electrolyte pellet. Next, the solid electrolyte pellet and the negative electrode layer obtained in each example were laminated together, and then molding pressure was applied to form a solid electrolyte layer. Then, lithium foil was laminated onto the solid electrolyte layer on the side opposite to the negative electrode layer, and then restrained with a restraining pressure of 3 MPa to obtain a half-cell.
[0083] [Cycle Test] Using the half-cells obtained for each example, cycle tests were performed under the following test conditions. The reaction resistance (after 1 cycle and 3 cycles) and the ratio of reaction resistance (reaction resistance after 3 cycles / reaction resistance after 1 cycle) for each example were determined, and the results are shown in Table 1. 《Test Conditions》 • 1 cycle = 0.1C charge / discharge × 3 times + 0.1C charge × 1 time + 1 / 3C discharge × 1 time • The reaction resistance between the active material and the solid electrolyte at a State of Charge (SOC) of 60% was measured. • Initial charge: 1400mAh / g (equivalent to 60% SOC) • Restraining pressure: 3MPa • Test temperature: 45℃
[0084] [Table 1]
[0085] Table 1 shows that Examples 1-4, which have a coating layer, exhibited lower reaction resistance in both the 1-cycle and 3-cycle tests compared to Comparative Example 1, which does not have a coating layer, indicating that the electron and ion conduction paths between the active material and the solid electrolyte were strengthened. Furthermore, the ratio of reaction resistance in the 3-cycle test to the 1-cycle test shows that Examples 1-3 suppressed the increase in reaction resistance compared to Comparative Example 1, indicating that forming a coating layer suppresses the peeling of the solid electrolyte due to volume changes in the active material. [Explanation of Symbols]
[0086] 1…Lithium-ion rechargeable battery (battery) 10...Positive electrode 11…Positive electrode layer 12...Positive electrode current collector 20...Negative electrode 21... Negative electrode layer 22...Negative electrode current collector 30…Solid electrolyte layer 50…Silicon-based active materials 60…Covering layer 100...Coated active material (negative electrode active material coated with a coating layer)
Claims
1. It contains a silicon-based active material and a solid electrolyte, At least a portion of the surface of the active material is covered by a coating layer, The coating layer contains a metallic element capable of forming an alloy with lithium, Negative electrode.
2. The negative electrode according to claim 1, wherein the metal element is at least one of Ni, In, Sb, and Bi.
3. The negative electrode according to claim 1, wherein the thickness of the coating layer is 10 nm or more and 100 nm or less.
4. The negative electrode according to claim 1, wherein the metal element is Sb.
5. The negative electrode according to claim 1, wherein the solid electrolyte is a sulfide solid electrolyte.
6. The negative electrode according to claim 1, wherein the active material is a composite material of silicon and a different element from silicon.
7. A lithium-ion secondary battery comprising a negative electrode, a positive electrode, and a solid electrolyte layer, as described in any one of claims 1 to 6.
Citation Information
Patent Citations
All-solid-state battery and method for manufacturing the same
JP7251069B2
Interconnected silicon porous structure for anode active material
US11223036B2
Stable lithium fluoride-based cathodes for metal and metal-ion batteries
US20200373580A1
Pre-lithiated silicon-carbon composite material, an anode comprising the same and a method to manufacture of a composite material
WO2023198886A1